Mandibular reconstruction with virtual planning and 3D models of a microsurgical fibula flap in pediatric patient: case report - Sotelo-Gonzáles, Eva S. (2025)
Odontogenic tumors are atypical benign neoplasms with a high potential for aggressiveness, originating from embryonic odontogenic tissue. Resection of these tumors involves the removal of part of the face, which may require reconstruction. Microsurgical reconstruction using the fibula osteocutaneous free flap is the most recommended technique in these cases. We present the case of a 14-year-old female patient with progressive growth of a facial tumor that resulted in difficulty swallowing and speaking, as well as intermittent oral bleeding. After deciding on tumor resection, virtual preoperative planning and three-dimensional printing modeling based on tomographic data were performed to enable a more precise reconstruction. The surgical approach consisted of a left hemimandibulectomy followed by microsurgical reconstruction with a fibula free flap. The postoperative course was favorable, and the outcome was satisfactory both anatomically and aesthetically. Histopathological analysis confirmed the tumor to be a cystic ameloblastoma. It is concluded that combining current technological advances with adequate preoperative planning achieves an optimal outcome for the patient. Few cases have been reported involving surgical reconstruction with virtual planning, as well as long-term follow-up of the patient. This pathology in the pediatric population represents a unique challenge, requiring intervention that preserves the natural development of the child.